2010
DOI: 10.1021/la102218w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fabrication of Bimetallic Spherical Motors

Abstract: Catalytic bimetallic nanomotors can swim at 100 body lengths per second as well as pick up, haul, and release micrometer-scale cargo. The electrokinetic locomotion of bimetallic nanomotors is driven by the electrocatalytic decomposition of hydrogen peroxide. The motors are typically fabricated by electrodeposition-based template synthesis techniques that result in heterogeneous samples and require specialized knowledge of electrochemistry, a three-electrode potentiostat setup, cyanide-based chemistry, and poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 31 publications
3
148
0
1
Order By: Relevance
“…We previously reported that spherical bimetallic motors swim in H 2 O 2 in the same manner as bimetallic nanorods [30]. In addition to the translational velocities typical of bimetallic nanomotors, the spherical motors are also observed to possess a rotational velocity.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…We previously reported that spherical bimetallic motors swim in H 2 O 2 in the same manner as bimetallic nanorods [30]. In addition to the translational velocities typical of bimetallic nanomotors, the spherical motors are also observed to possess a rotational velocity.…”
Section: Resultsmentioning
confidence: 79%
“…The motor translational swimming velocities are shown in Fig. 2 in hydrogen peroxide [6,26,27,30,36]. The motor angular velocities are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations